2008
DOI: 10.12968/npre.2008.6.6.29610
|View full text |Cite
|
Sign up to set email alerts
|

Development of nurse-led clinics in genitourinary medicine

Abstract: The role of the nurse is evolving, and nurses are increasingly undertaking responsibilities traditionally carried out by medical personnel. One area of practice in which nurses' roles have become more advanced is genitourinary medicine (GUM), with the development of nurse-led GUM clinics. There has been an escalating incidence of sexually transmitted infections (STIs) and HIV in society, despite a concerted improvement in accessibility and delivery of GUM services. This has led to a greater pressure on GUM dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Many researchers have found that the inclusion of CNSs in the care of patients improves patient satisfaction 12 18 related to improved standards and quality of care and better multidisciplinary team communication. 13 15 , 19 CNSs influence all aspects of the patient care environment including facilitating functionality of the multidisciplinary team. 20 An audit of patient satisfaction with CNS-led services after ileoanal pouch surgery found that 90% of patients were very satisfied with this service.…”
Section: Impact Of Specialist Nursing Practice On Patient Carementioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have found that the inclusion of CNSs in the care of patients improves patient satisfaction 12 18 related to improved standards and quality of care and better multidisciplinary team communication. 13 15 , 19 CNSs influence all aspects of the patient care environment including facilitating functionality of the multidisciplinary team. 20 An audit of patient satisfaction with CNS-led services after ileoanal pouch surgery found that 90% of patients were very satisfied with this service.…”
Section: Impact Of Specialist Nursing Practice On Patient Carementioning
confidence: 99%
“… 16 The same was also found in patients attending nurse-led genitourinary clinics. 15 In a study of diabetes nurse-led clinics, it was found that CNSs reduced the 10-year disease risk scores by managing uncontrolled hypertension compared to usual care. 21 Hill et al compared care provided by CNSs and a junior doctor; patients with rheumatoid arthritis had higher scores for patient satisfaction and improved quality of care in the CNS group.…”
Section: Impact Of Specialist Nursing Practice On Patient Carementioning
confidence: 99%